Pengaruh Output Pertanian Dan Pariwisata Terhadap Pertumbuhan Ekonomi Di Indonesia - Haryani Haryani; Asrida Asrida (Fakultas Ekonomi Universitas Almuslim Bireuen, 2021)
This research aims to explain the influence of agricultural output and tourism on growth Indonesian economy. To get maximum results, the data used is secondary data which are time series, namely data on economic growth, agricultural output and tourism data Data used on the number of foreign tourist arrivals in Indonesia over the last 24 years, namely yr 1995-2019 sourced from the World Bank using multiple linear regression analysis techniques. Research result shows that agricultural output and tourism have a positive effect on economic growth in Indonesia